A Critical Review on the Progress of Kesterite Solar Cells: Current Strategies and Insights. Issue 2 (20th November 2022) - Wang, Ao; He, Mingrui; Green, Martin A.; Sun, Kaiwen; Hao, Xiaojing
Abstract: Kesterite Cu2 ZnSn(S, Se)4 (CZTSSe) with earth‐abundant and environmental‐benign constituents has been regarded as a promising solar energy harvesting material for green and cost‐effective photovoltaic applications. The record efficiency of CZTSSe solar cells has recently been refreshed twice after years‐long stagnation, keeping it in the spotlight. Nevertheless, the champion efficiency of 13.6% is still far behind its counterpart Cu(In, Ga)Se2 (CIGS) (23.35%) despite being endowed with a similar electronic structure and nearly‐identical device architecture. In fact, CZTSSe solar cells are more susceptible to non‐radiative recombination at bulk and interfaces, which must be improved for further efficiency advancement. In this review, the state‐of‐art strategies to enhance the power conversion efficiency of CZTSSe solar cells are summarized and discussed, with focus given to three critical device regions i) kesterite absorber, ii) buffer/kesterite interface, and iii) kesterite/back contact interface. With the further elucidation of the latest progress and disclosure of fundamental mechanisms, novel insights toward high‐efficiency kesterite solar cells are proposed. Abstract : State‐of‐art strategies addressing the dominant recombination in kesterite Cu2 ZnSn(S, Se)4 solar cells are reviewed. Attention is focused on the kesterite absorber, front p‐n heterojunction, and kesterite/back contact interface, as they primarily limit the performance of kesterite devices and can be improved simultaneously. By systematically scrutinizing these highly compatible measures, promising research directions are proposed to stimulate further progress and strategy integration.